INTERNATIONAL LEGAL FOUNDATIONS FOR THE PREVENTION OF JUVENILE DELINQUENCY - Abdurasulova Kumrinisa Raimkulovna (Modern American Journals, 2025)
The article examines the international legal foundations for protecting the rights and freedoms of minors and their role in preventing juvenile delinquency. It analyzes key international documents regulating children’s rights, including the UN Convention on the Rights of the Child, ILO conventions, UN declarations, and guidelines. The importance of international standards in improving the national legislation of Uzbekistan and developing effective mechanisms for safeguarding children’s rights is emphasized. The article presents statistical data on violations of children’s rights worldwide, identifies challenges in implementing international requirements at the national level, and proposes measures to enhance the effectiveness of law enforcement and legal protection of minors.
Keywords: International legal foundations; children’s rights; minors; prevention of juvenile delinquency; UN Convention on the Rights of the Child; international instruments; ILO; child protection; national legislation; Uzbekistan; juvenile policy.